Regresi Data Panel untuk Mengetahui Faktor-Faktor yang Mempengaruhi IPM di Kabupaten/Kota Provinsi DIY - Epha Diana Supandi; Riska Yulianti; Akhmad Fauzy (Department of Statistics, Faculty of Mathematics and Natural Sciences, Universitas Islam Bandung, 2022)
The Human Development Index (HDI) is a regional or national welfare index based on three aspects, namely a long and healthy life, knowledge, and a decent standard of living. This study aims to determine the factors that affect the HDI of Regency/City in the Province of the Special Region of Yogyakarta (DIY) in 2016-2021. These factors include poverty rates, average length of schooling, gross regional domestic product, and health complaints. The analysis used is panel data regression. The influencing factors are the variable of poverty level, average length of schooling and gross regional domestic product.